The Quick & Easy Way to Effective Speaking : Modern Techniques for Dynamic Communication - Carnegie, Dale (New York Pocket Books, 1977)
Shows the fundamentals on how to be a brilliant speaker.
Keywords: Public speaking -- Business presentations -- Communication